Editorial for special issue "finance, financial risk management and their applications" - Leunglung Chan (International Journal of Financial Studies, 2018)
We are pleased to announce the Special Issue on the Finance, Financial Risk Management and their Applications in the International Journal of Financial Studies. This Special Issue collects papers pertaining to several lines of research related to finance and financial risks. This Guest Editor's note synthesizes the contributing authors' propositions and findings regarding these developments and hopes that new areas can be opened for future researches.
Keywords: 330